2014
DOI: 10.1371/journal.pone.0113706
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Tumor Cell Subpopulations in Patients with Head and Neck Squamous Cell Carcinoma (HNSCC)

Abstract: BackgroundSince image based diagnostic tools fail to detect early metastasis in head and neck squamous cell carcinoma (HNSCC) it is crucial to develop minimal invasive diagnostic methods. A promising approach is to identify and characterize circulating tumor cells (CTC) in the peripheral blood of HNSCC patients. In this pilot study, we assessed which non-hematopoietic cell types are identifiable and whether their numbers differ in pre- and postoperative blood samples.Methods20 ml citrated peripheral blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 31 publications
2
41
1
2
Order By: Relevance
“…This contributes to the great variation in detection levels of CTCs in HNSCC depending on method . Earlier studies have shown that there is a negative correlation between increased number of CTCs and survival but they do not add prognostic or predictive value beyond what is already achieved with TNM status . Therefore, simple CTC measurements as performed so far has not proven to give any specific new information that can be used for determining the treatment in the individual case of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…This contributes to the great variation in detection levels of CTCs in HNSCC depending on method . Earlier studies have shown that there is a negative correlation between increased number of CTCs and survival but they do not add prognostic or predictive value beyond what is already achieved with TNM status . Therefore, simple CTC measurements as performed so far has not proven to give any specific new information that can be used for determining the treatment in the individual case of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…They are rare cells amongst a high number of blood cells, and require specialized means for identification . Enumeration of CTCs can be carried out with a variety of assays, including density gradient centrifugation, immunomagnetic isolation and microfluidics . Many technologies for CTC detection are based on negative selection of white blood cell surface markers (especially CD45) and positive selection of epithelial cell surface markers (especially EpCAM and cytokeratin) .…”
Section: Next‐generation Biomarkers Of Mibcmentioning
confidence: 99%
“…These may result in a second invasive cancer or residual cancer cells remaining in the surgical wound in unde-tectable numbers (minimal residual cancer). 2 Another possible source is circulating tumor cells, [3][4][5][6][7][8][9][10][11][12][13] introduced to the vascular system before and during surgery. From there, they are supposedly able to enter, and establish growth in, the environment provided by a healing wound, rich in epidermal growth stimuli, in analogy with the tumor self-seeding hypothesis.…”
Section: Introductionmentioning
confidence: 99%